The development of an experimental conscientiousness measurement instrument within the SAPI project - Janse van Rensburg, Charnelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2011.